L'innovation d'un MOOC en sciences de gestion : vers une approche systémique basée sur la co-création de valeur entre acteurs - Sabrina Hombourger-Barès; Patrick Pelletier; Christine Simard; Lucie Moulet
This article sheds new light on the understanding of the processes of innovative distance learning in higher education via an in-depth case study relating to the development of a MOOC. It reveals that, at present, current models are based on a traditional conception of innovation. Despite the role of key actors being clearly defined and demonstrated, previous studies do not fully acknowledge the collective nature and social aspects of innovation. Using a systematic approach to innovation, this case study presents institutional logics and organizational rationalities that have shaped the innovative process. Additionally, it illustrates the central role of value co-creation amongst actors in multiple operational activities. Finally, it upholds the importance of support resources, self-determination and collective action in the innovation process.